Pendidikan Keimanan kepada Al-Qur’an : Surah Al-Baqarah Ayat 2 - Zainul Anwar (Mentari : Journal of Islamic Primary School, 2023)
Religious education is the process of shaping and developing faith in God, religion, and the principles of the believed religion.The Quran is the primary source of Islamic teachings that teach how to live according to Allah's guidance, including how to worship, act justly, and respect the rights of others. The Quran also provides guidance on the importance of deepening religious knowledge and teaches to seek and understand the teachings contained within it. The religious teachings described in the Quran emphasize the importance of living according to Islamic teachings and expecting rewards in the afterlife. The purpose of this article is to understand how religious education is interpreted by Ibn Kathir regarding Surah Al Baqarah verse 2 of the Quran. This article was written using the literature research method through content analysis. After going through the revision process, it can be concluded that the interpretation of this verse contains elements of faith, namely honor for the righteous and teachings or guidance.